Disruption of mycorrhizal extraradical mycelium and changes in leaf water status and soil aggregate stability in rootbox-grown trifoliate orange - Zou, Ying-Ning; Srivastava, A. K.; Ni, Qiu-Dan; Wu, Qiang-Sheng (Frontiers in Microbiology, 2015)
Arbuscular mycorrhizas possess well developed extraradical mycelium (ERM) network that enlarge the surrounding soil for better acquisition of water and nutrients, besides soil aggregation. Distinction in ERM functioning was studied under a rootbox system, which consisted of root+hyphae and root-free hyphae compartments separated by 37-μm nylon mesh with an air gap. Trifoliate orange (Poncirus trifoliata) seedlings were inoculated with Funneliformis mosseae in root+hyphae compartment, and the ERM network was established between the two compartments. The ERM network of air gap was disrupted before 8 h of the harvest (one time disruption) or multiple disruptions during seedlings acclimation. Our results showed that mycorrhizal inoculation induced a significant increase in growth (plant height, stem diameter, and leaf, stem, and root biomass) and physiological characters (leaf relative water content, leaf water potential, and transpiration rate), irrespective of ERM status. Easily-extractable glomalin-related soil protein (EE-GRSP) and total GRSP (T-GRSP) concentration and mean weight diameter (MWD, an indicator of soil aggregate stability) were significantly higher in mycorrhizosphere of root+hyphae and root-free hyphae compartments than non-mycorrhizosphere. One time disruption of ERM network did not influence plant growth and soil properties but only notably decreased leaf water. Periodical disruption of ERM network at weekly interval markedly inhibited the mycorrhizal roles on plant growth, leaf water, GRSP production, and MWD in root+hyphae and hyphae chambers. EE-GRSP was the most responsive GRSP fraction to changes in leaf water and MWD under root+hyphae and hyphae conditions. It suggests that effect of peridical disruption of ERM network was more impactful than one-time disruption of ERM network with regard to leaf water, plant growth, and aggregate stability responses, thereby, implying ERM network aided in developing the host plant metabolically more active.